2014
DOI: 10.1007/s00170-014-6120-0
|View full text |Cite
|
Sign up to set email alerts
|

Chatter in interrupted turning with geometrical defects: an industrial case study

Abstract: In this paper, machine tool chatter arising in an interrupted turning process is investigated in a strong industrial context with a complex flexible part. A detailed analysis of the real cutting process is performed with special respect to the geometrical defects of the part in order to highlight the source of machine tool vibrations. The analysis is completed by simple models to estimate the forced vibrations in interrupted turning, the gyroscopic effect, and the mode coupling using a new simplified formulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…This mechanism, called the regenerative effect, has been first explained by Tobias and Fishwick [3] and is mainly responsible for chatter instability. Since these works, many researchers have improved the knowledge by the well known stability lobe representation and its application to special cases [4][5][6][7][8][9][10]. A detailed nonlinear analysis of chatter instability on turning processes has been carried out in [11] using the method of multiple scales.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism, called the regenerative effect, has been first explained by Tobias and Fishwick [3] and is mainly responsible for chatter instability. Since these works, many researchers have improved the knowledge by the well known stability lobe representation and its application to special cases [4][5][6][7][8][9][10]. A detailed nonlinear analysis of chatter instability on turning processes has been carried out in [11] using the method of multiple scales.…”
Section: Introductionmentioning
confidence: 99%
“…The optimization of the machine tool design has been studied by incorporating the FE models for full machine analyses with the consideration of machining stability in process [19,20]. Studies of Mousseigne et al, [21,22] found the variation of the tool point dynamic response with the change of milling, which further caused great influences on the stability lobe curves. Their study also suggested that a precise estimation of the natural frequencies is of importance for lessening the uncertainty of the stability lobe curves.…”
Section: Introductionmentioning
confidence: 99%
“…A novel dynamic cutting force model is proposed by Li et al [13], in which the cutting mechanism and the cutting force contribution on both the peripheral and the front cutting edges are taken into consideration simultaneously. An interrupted turning cutting force model was proposed and a detailed analysis of the stability was performed by Seguy et al [14]. In the above studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14], the cutting force models are linear, without considering nonlinearities in terms of chip thickness.…”
Section: Introductionmentioning
confidence: 99%
“…An interrupted turning cutting force model was proposed and a detailed analysis of the stability was performed by Seguy et al [14]. In the above studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14], the cutting force models are linear, without considering nonlinearities in terms of chip thickness. Given this, powerlaw function for cutting force was used to analyse chatter by Hanna and Tobias [15] and Stépán et al [16] and Yang et al [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation